Returning life : language, life force and history in Kilimanjaro - Myhre, Knut Christian, 1971- (Methodology and history in anthropology, 2018)
A group of Chagga-speaking men descend the slopes of Mount Kilimanjaro to butcher animals and pour milk, beer, and blood on the ground, requesting rain for their continued existence. Returning Life explores how this event engages activities where life-force is transferred and transformed to afford and affect beings of different kinds. Historical sources demonstrate how the phenomenon of life-force encompasses coffee cash-cropping, Catholic Christianity, and colonial and post-colonial rule, and features in cognate languages from throughout the area. As this vivid ethnography explores how life projects through beings of different kinds, it brings to life concepts and practices that extend through time and space, transcending established analytics.--Publisher's summary.